New records and noteworthy data of plants, algae and fungi in SE Europe and adjacent regions, 10 - Gordana Tomović; Marko S. Sabovljević; Irina Irimia; Hatıra Taşkın; Eva Zupan; Petya Boycheva; Dobri Ivanov; Beata Papp; Jovana Pantović; Aleksandra Marković; Sanja Z. Djurović; Uroš Buzurović; et al. (Botanica Serbica, 2022)
This paper presents new records and noteworthy data on the following taxa in SE Europe and adjacent regions: red algae Lemanea rigida and Paralemanea torulosa, mycorrhizal fungi Amanita simulans and Terfezia pseudoleptoderma, parasitic fungus Microbotryum vinosum, saprotrophic fungus Sarcoscypha jurana, stonewort Chara tenuispina, mosses Brachytheciastrum collinum and Meesia longiseta, monocots Dactylorhiza romana and Neotinea maculata and dicots Adenophora liliifolia, Ambrosia artemisiifolia and Tanacetum corymbosum subsp. cinereum are given within SE Europe and adjacent regions.